2004
DOI: 10.1080/16501970310018314
|View full text |Cite
|
Sign up to set email alerts
|

From shame to respect: musculoskeletal pain patients' experience of a rehabilitation programme, a qualitative study

Abstract: The rehabilitation programme started the process of change, from shame to respect. The informants learned new strategies for handling their pain and other symptoms; they improved their self-image and communication in their social environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
80
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 23 publications
7
80
0
2
Order By: Relevance
“…We did not include papers that did not meet our criteria for inclusion, and included an additional nine fibromyalgia studies. 324,327,335,351,352,366,373,377,381 Their synthesis supports important areas of our conceptual analysis, for example the 'conscious awareness' of the body in pain; the unrelenting nature of fibromyalgia; isolation and loneliness; the search for an diagnosis; the ambiguity of diagnosis and loss of legitimacy. It also supports concepts related to moving forward with pain, including listening to the body, accepting loses and re-evaluating life.…”
Section: Qualitative Syntheses In Musculoskeletal Painmentioning
confidence: 97%
See 2 more Smart Citations
“…We did not include papers that did not meet our criteria for inclusion, and included an additional nine fibromyalgia studies. 324,327,335,351,352,366,373,377,381 Their synthesis supports important areas of our conceptual analysis, for example the 'conscious awareness' of the body in pain; the unrelenting nature of fibromyalgia; isolation and loneliness; the search for an diagnosis; the ambiguity of diagnosis and loss of legitimacy. It also supports concepts related to moving forward with pain, including listening to the body, accepting loses and re-evaluating life.…”
Section: Qualitative Syntheses In Musculoskeletal Painmentioning
confidence: 97%
“…66,312,323,325,326,330-334,336,338,342-345,350,353-358, 362-365,367,372,374,376,379,385-387 Twenty-eight papers (23 individual studies) explored the experience of people with fibromyalgia. 324,[327][328][329]335,337,[339][340][341]346,349,351,352,[359][360][361]366,373,375,377,378,[380][381][382][383][384] A description of these studies is provided in Tables 6 and 7, showing for each study the age range and source of participants, the country where the study was carried out, the method of data collection and the methodology used. …”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Support and understanding of colleagues and the supervisor is crucial according to workers themselves [7,13,14,15,16]. A negative self-image, feelings of hopelessness related to employability and inability to set limits were mentioned by workers with musculoskeletal pain [17]. Reluctance to disclose health information to others and fear that colleagues may see them as unfairly favoured was mentioned by patients with inflammatory arthritis [16].…”
Section: Introductionmentioning
confidence: 99%
“…The potential shame of the patient is a barrier that has to be overcome by all in health-care encounters. Persons with musculoskeletal illnesses associated with pain often report feelings of shame when physicians doubt their wish to recover (Gustafsson et al, 2004). On the basis of interviews with persons on long-term sick leave Vidman (2009) has found that her respondents, in addition to the limitations resulting from their symptoms, had to deal with distrust due to the invisibility of their impairments, which made it hard for others to understand.…”
mentioning
confidence: 99%